The Borders of Reading: Reading Literature at the University - Cruz, Mery (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This paper presents the design and implementation of a Literary Constellation with university students, based on a corpus of texts that address violence, women and undocumented immigrants as references. The aim was to foster scenarios of democratic participation through literary conversations, as well as the possibility of experiencing the otherness that aesthetic languages stimulate. The methodology for systematizing the experience followed the ethnographic analysis of the dialogues that took place in the classes; in this way, it was shown that, rather than individuality, it is sharing with others that can arouse feelings of empathy and compassion towards situations of human vulnerability recreated by literature. The reading practice described above suggests that it is a form of mobilization for engaging in discussion and dialogue with the diverse perspectives that exist in specific school populations; this aims to create or enhance democratic spaces of interaction.